Language Encyclopedia on Fable Story Material to Develop Creative Thinking Skills in Grade II Students - Serafika, Angella Caroline; Setiawan, Dwi Agus Setiawan; Delawanti , Denna (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to develop a Language Encyclopedia media to foster creative thinking skills that are appropriate for Indonesian language subjects on fable material. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were second-grade students and second-grade teachers of SD Negeri 01 Wirotaman, Ampelgading. Data collection methods used observation and questionnaires. The instruments used in this study were validation questionnaire sheets and teacher response questionnaires. The questionnaire sheets of experts or validators used a 4-point scale ranging from less to very good. From the results of the validation assessment by media experts obtained 94% with a very valid category, by language experts obtained 80% with a valid category, by material experts obtained 82% with a very valid category. Meanwhile, in the results of the practicality test by teachers obtained 88% with a very practical category and students obtained 82% with a very practical category. So this media is said to be valid and practical for use in learning. Teachers can use this language encyclopedia media to foster creative thinking skills.